Nutritional Quality Evaluation of Cowpea Supplemented Food Products - Kushwaha, Archana; Verma, Astuti; Kumar, Anil (Journal of Postharvest Technology, 2014)
An experiment was conducted to develop and evaluate nutritional  and sensory characteristics of food products supplemented with  cowpea flour. Cowpea flour was incorporated at the levels of  20%, 40%, 60% and 80% to products made from whole wheat  flour in khajure, semolina in halwa and refined wheat flour in  mathri. Products prepared without cowpea flour served as  control. Cowpea flour incorporation levels of 20%, 40% and 20%  for khajure, mathri and halwa, respectively, was found to be  significantly acceptable. Nutrient composition of acceptable  cowpea supplemented food products show an increase in protein,  fibre, calcium, iron , magnesium and zinc content ranging from  5.3-13.0%, 0.4 -1.5 %, 16.1-89.2%, 1.3-5.5%, 31.8-98.4% and  0.7-1.8%, respectively as compared to their control counterparts.  Present study indicates that cowpea supplemented food products  could be considered the best from both nutritional and sensory  points of view, especially for young children.
Keywords: Cowpea; Supplementary foods; Nutrient composition; Sensory evaluation